2008
DOI: 10.1128/jb.01638-07
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniaeGroEL1 Protein Is Cell Surface Associated and Required for Infection of HEp-2 Cells

Abstract: Chlamydia pneumoniae is an important obligate intracellular pathogen that replicates within an inclusion in the eukaryotic cell. The initial event of a chlamydial infection is the adherence to and subsequent uptake of the infectious elementary bodies (EBs) by the human cell. These processes require yet-unidentified bacterial and eukaryotic surface proteins. The GroEL1 protein, which exhibits a very strong antigenicity and in vitro can activate various eukaryotic cells, is a potential pathogenicity factor. We l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 88 publications
(88 reference statements)
3
38
0
Order By: Relevance
“…Our study confirmed that following bacterial attachment, typical inclusions formed that were permissive to bacterial growth, resulting in increased infectious progenies in [17][18][19][20][21][22]. Heparin, which forms the majority of GAGs, also plays a critical role in host cells as a receptor for the attachment of the other pathogens such as Bordetella pertussis [35], Hemophilus influenzae [36] or Neisseria gonorrhoeae [37].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Our study confirmed that following bacterial attachment, typical inclusions formed that were permissive to bacterial growth, resulting in increased infectious progenies in [17][18][19][20][21][22]. Heparin, which forms the majority of GAGs, also plays a critical role in host cells as a receptor for the attachment of the other pathogens such as Bordetella pertussis [35], Hemophilus influenzae [36] or Neisseria gonorrhoeae [37].…”
Section: Discussionsupporting
confidence: 65%
“…Heparin independent attachment and host invasion has also been described for the C. trachomatis LGV invasive serotype causing a systemic disease, but not for any other serotypes [17][18][19][20][21][22]. This suggests that a heparin-independent attachment mechanism is useful for a pathogen to effectively spread from local lesions, such as the genital tract in this case, to other distinct lymphoid tissue, as observed in pelvic inflammatory disease [42].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The discovery that EBs can translocate stored proteins into the host under distinct signaling pathways is further evidence that the entry process results from a dialogue between the bacteria and the host, although many features including EB protein attachment to target cells remain to be clarified or discovered [33,34].…”
Section: Chlamydia Morphology and Functionmentioning
confidence: 99%